An Overview of the Impact of Vibrations on Li‐Ion Battery Performance, Degradation, Battery Thermal Management System and Key Focus Areas - Boozula Aravind Reddy (Engineering Reports, 2025)
ABSTRACT Lithium‐ion batteries (LIBs) have gained significant attention in recent years due to their widespread applications in electric vehicles, portable electronics, energy storage, and renewable energy systems. However, their increasing use raises concerns about safety, reliability, and performance under various operating conditions. Among these, the impact of vibrations encountered during transportation, operation in vehicles, and industrial environments on battery performance, state of charge (SoC) and other critical parameters is of particular importance. This study is an overview that focuses on understanding the effects of vibrations on Li‐ion batteries (especially cylindrical, pouch, and prismatic cells) through a combination of experimental testing and simulation modeling results. The experimental results highlight the influence of vibration‐induced stress on electrical performance and battery degradation behavior. Simulations complement these findings by providing insights into the mechanical and electrochemical responses, effect on battery thermal management systems under different vibration frequencies and amplitudes. By addressing these effects comprehensively, this overview aims to contribute to the design of more robust Li‐ion battery systems capable of withstanding dynamic environments. The experimental studies show that discharge capacities were consistently decreasing depending on the cycles, frequencies, and the amplitudes of vibrations; this could be attributed to the separator and graphite anode material degradation. Also, the simulation results showed that the battery temperature management systems will be more effective under vibration conditions.